Aliphatic and polycyclic aromatic hydrocarbons in surficial sediments of Bahía de Todos Santos, B. C., México. - Villegas Jiménez, A.; Macías Zamora, J. V.; Villaescusa Celaya, J. A. (HIDROBIOLÓGICA, 2016)
The levels of concentration and distribution patterns of aliphatic (n-hydrocarbons) and polycyclic aromatic hydrocarbons (or PAH’s) were determined in 16 samples of recent marine sediments of Bahía de Todos Santos, Baja California. The purpose was to stablish base line data as a future reference. We report here on our findings. The extraction was carried out by means of a solid phase extraction procedure reported by Burrows (1983) both for cleaning and separation of fractions of compounds. For identification and quantification of compounds we used capillary gas chromatography with FID detection for both fmilies of molecules. The concentrations found within the Bay were relatively small and homogeneous (from 0.1 to 2.6 mg g1). Cluster analysis suggests three significantly different zones. The indexes used for source identification of hydrocarbons are presented and discussed. Possible origins for these materials are discussed. Similarly, possible explanations are offered on the fluxes suggested by the isophlets. The overall conclusion is that the Bay can be considered as a relatively clean bay with respect to hydrocarbon pollution and that anthropogenic (or even natural) processes have not a major impact on the Bay.